Isogeometric analysis-based approaches for fracture and contact problems of structures and materials - Huang, Jiazhao (Nanyang Technological University, 2020)
The field of fracture mechanics focuses on investigating the crack initiation and propagation in materials. Since the presence of cracks within materials cannot be precluded during the manufacturing processes, the mechanical and physical properties of engineering structures would be significantly affected by cracks, resulting in the fractures of these structures. Contact mechanics is another important subject of engineering as many mechanical components are operating under contact loading conditions. Analysis of stress and deformation induced by contact loading is complicated due to its multi-scale and multi-physical nature. For both fracture and contact problems, isogeometric analysis (IGA) has been developed as a promising computational tool that exhibits significant advantages in terms of geometry exactness, high-order approximation and tailorable inter-element connectivity. This Ph.D. study aims at developing IGA-based solutions for fracture and contact problems of structures and materials.